The Effect of Job Analysis and Career Development Through Competency on Employee Performance - Erwan, Erwan; Zahari, M.; Hapsara, Osrita (Dinasti Publisher, 2024)
The objectives of this study are: 1) to describe job analysis (JA), career development, competencies, and employee performance; 2) to analyze the direct and indirect effects of job analysis (JA) and career development on competencies; 3) to assess the direct and indirect effects of job analysis (JA) and career development on employee performance; 4) to determine the effect of competencies on employee performance; and 5) to evaluate the effect of job analysis (JA) and career development on employee performance through competencies. The research method employed descriptive and verificative analysis with a path analysis approach. The sample consisted of 62 respondents, and data were collected through a census survey using a questionnaire. The findings of the study are as follows: 1) The variables of job analysis, career development, and competencies are in fairly good condition, while performance is categorized as moderate; 2) Job analysis (JA) and career development have direct and indirect effects on competencies; 3) Job analysis and career development have both direct and indirect effects on employee performance; 4) Competencies have an effect on employee performance; 5) Job analysis and career development through competencies impact employee performance.